If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -3 + xy + 3x = 5 Reorder the terms: -3 + 3x + xy + 2y = 5 Solving -3 + 3x + xy + 2y = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3x + xy + 3 + 2y = 5 + 3 Reorder the terms: -3 + 3 + 3x + xy + 2y = 5 + 3 Combine like terms: -3 + 3 = 0 0 + 3x + xy + 2y = 5 + 3 3x + xy + 2y = 5 + 3 Combine like terms: 5 + 3 = 8 3x + xy + 2y = 8 Add '-2y' to each side of the equation. 3x + xy + 2y + -2y = 8 + -2y Combine like terms: 2y + -2y = 0 3x + xy + 0 = 8 + -2y 3x + xy = 8 + -2y Reorder the terms: -8 + 3x + xy + 2y = 8 + -2y + -8 + 2y Reorder the terms: -8 + 3x + xy + 2y = 8 + -8 + -2y + 2y Combine like terms: 8 + -8 = 0 -8 + 3x + xy + 2y = 0 + -2y + 2y -8 + 3x + xy + 2y = -2y + 2y Combine like terms: -2y + 2y = 0 -8 + 3x + xy + 2y = 0 The solution to this equation could not be determined.
| 9xy+9xy= | | 3xy-x+9y+2=0 | | 4x^2+8x-4=100 | | log(10)x=0.6 | | -3x^2=-7x+12 | | 3x*y-x+9y+3=13 | | 3.1x-4=2.1x | | (2x^2+1x)+(6x+6)=0 | | ((2x^2)+1x)+(6x+6)=0 | | -3+(-3x)=18 | | 5+.50s=1s | | -5y+1(2)=5 | | -(2-8x)=3(8x-1)-16x+1 | | t(n)=-8-7(447) | | -3x-2(5y-7)=-12 | | -5+3x=3(x-6)+13 | | 180(n-2)=156 | | t(n)=14-3(447) | | 6w=8w-40 | | 1.04x/3.14=7.98 | | 19u-17u-u=20 | | 3x^3-x*y=5 | | x+6=x-4 | | ln8/ln4 | | ln8/lnr4 | | ln8/lv4 | | 9m+10-4m=-5 | | (5/9)x^2-(16/5)x-3/2=0 | | 10s-6s-3s-1=13 | | 3(8-x)-5=-6x-4+3n | | 3x-10+2x=-65 | | t(n)=-6+3(447-1) |